Synthetic Approaches to Unsymmetrically Substituted 5,7-Dihydroxycoumarins - Fatykhov, Ramil F.; Chupakhin, Oleg N.; Inyutina, Anna K.; Khalymbadzha, Igor A. (Synthesis, 2020)
The chemical equivalence of the hydroxy groups in the 5,7-dihydroxycoumarin core has challenged synthetic chemists to develop short and efficient strategies for the selective modification of one of the hydroxy groups leaving the second intact. Over the past 100 years, chemists have proposed various approaches to distinguishing between these two groups according to their reactivity. While the early syntheses included simple nonselective reactions of both hydroxy groups and the subsequent separation of mixtures of the 5-O- and 7-O-isomers formed, recent sophisticated approaches often include the introduction of protective groups for selective directing reactions or the completely controlled construction of the 5,7-dihydroxycoumarin framework by Horner–Wadsworth–Emmons reaction. This review discusses in detail approaches towards unsymmetrically substituted 5,7-dihydroxycoumarins as well as factors influencing 5-O vs. 7-O regioselectivity of reactions of 5,7-dihydroxycoumarins. This review covers all the literature since 1921 with an emphasis on recent works. This critical review may facilitate the synthesis of new drug candidates as well as the total synthesis of natural products.1 Introduction2 O-Modification of 5,7-Dihydroxycoumarins2.1 Alkylation/Alkenylation2.2 Acylation2.3 Sulfonylation2.4 Silylation2.5 Acylation Followed by Alkylation3 Other Approaches3.1 Synthesis from Substituted Phloroglucinol3.2 Synthesis from Derivatives of 2-Acylphloroglucinol4 Conclusion
Keywords: regioselective reactions; coumarin; protective groups; natural products